História da literatura e identidade nacional brasileira / Literary history and Brazillian national identity - Moreira, Maria Eunice (Revista de Letras, 2007)
O texto analisa alguns aspectos teóricos da Historia d Literatura, num primeiro momento, para, na segunda parte, enfocar os historiadores estrangeiros e brasileiros, pioneiros na proposição de uma historia da literatura para o Brasil e, finalmente, na terceira parte, associar a questão historiográfica à realidade política do segundo Império, procurando discutir o papel do discurso historiográfico na identidade nacional brasileira.. This study has a threefold structure. First, some theoretical aspects of Literary History are analyzed. Then, the focus shifts to the Brazilian and foreign historians who pioneered the proposition of a Brazilian literary history. Finally, in the third part, the historiographic question is associated to the political reality of the Second Empire, ia an attempt to discuss the role of historiographic discourse in the construction of the Brazilian national identity.